(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
Zidovudine (AZT) mucoadhesive solid dispersions (SD) were prepared using a sodium starch glycolate (SSG) and hypromellose phthalate (HPMCP) mixtures as carrier to enhance the intestinal permeability and bioavailability of zidovudine. SDs were prepared using the co-precipitation method followed by solvent evaporation and characterized according to their physicochemical properties such as particle size, crystallinity, thermal behavior, and liquid uptake ability. In vitro drug dissolution, mucoadhesiveness and AZT intestinal permeability were also determined. Thermal behavior and X-ray diffraction patterns demonstrated the amorphous state of AZT in SD systems. The HPMCP polymer restricted the liquid uptake ability in the acid medium; however, this property significantly increased with higher pH values. SDs allowed drug dissolution to occur in a controlled manner. HPMCP decreased the dissolution rates in the acid medium. The mucoadhesiveness of SDs was demonstrated and the permeability of AZT carried in solid dispersions was significantly improved. The effect of the SD carrier polymers on blocking efflux pump can be an important approach to improve the bioavailability of AZT.